شیكردنەوەی جوگرافی بۆ گەشەى سروشتی دانیشتوانى شارى سەیدسادق - حسین, پ.ی.د.بەیان علی; عبداللە, م.ی. هەورامان كمال میرزا (Sulaimani Journal for Humanities, 2023)
The natural growth of the population of cities, is one of the main factors addressed by population studies, especially those studies that are concerned with issues arranged by population growth, so now the natural growth of the population comes at the forefront of the elements that contribute to the growth of the population in general in any region or any city, On the other hand, population growth affects - in one way or another on the social, economic and political aspects of the population in any society, and this growth leaves its effects on the services provided by the state to the population, and this study aims to review the changes resulting from the high growth rate addressing the factors that are related in one way or another to the phenomenon of natural growth, The study of this phenomenon is useful to researchers and security authorities in developing future plans necessary for development. In order to reach this goal, the study relied on the "analytical study method and comparative study To reach the goal of the study".the researcher divided the study into three axes, the first axis deals with births, the second axis deals with the phenomenon of mortality, and the third axis deals with the natural growth of the population in the study area, and finally the study has reached the presentation of the necessary results and suggestions.